Kajian Teologis Kegagalan Pendangan Umum Yang Mengusung Yohanes Pembaptis Sebagai Mesias - Feri Dolf Djami Hae; B.D Nainggolan; Stimson Hutagalung; Rolyana Ferinia (JURNAL KADESI, 2021)
Jesus asked his disciples, saying, “Whom do men say that I the Son of man am?” (Matt. 16:13, Mark. 8:27), then John the Baptist was the top answer, followed by Elijah, Jeremiah. This study uses a biblical study of the meaning of the whom do men say (general opinion) by using a qualitative writing method that is studied by biblical exegesis supported by various sources related to this research. Here it is found that public opinion greatly influences one's personal belief and confession of their faith in Jesus Christ. There is a meaning behind the rejection of Jesus' messiahship by carrying the popular John the Baptist figure. Perhaps if he announced himself as the Messiah, and waged a rebellion against the Roman empire which was colonizing Israelit at that time, it would be inconceivable if that happened. Researchers found the answer that the importance of personal spiritual experience closely with God between times when the truth became unpopular. By adhering to the Word of God, the Church of God can stand firm which is built on a solid rock foundation (Petra), namely Jesus Himself.